Indian Muslims’ Support for Ottoman Pan-Islamism: The Case of Shibli Nu’mani - Islam, Arshad (Intellectual discourse, 2019)
Following their violent suppression of the Indian Revolution of1857, the British founded and consolidated their secular empire in the IndianSubcontinent, which marginalized and bypassed religion as far as possible,particularly Islam, which had been the official religion of the Mughal ancienrégime. Contemporaneous Ottoman efforts to counter European imperialism ledto Sultan Abdul Hamid II’s (r. 1876-1909) policy of pan-Islamism, particularlythe call for Islamic unity against the Russian aggression against Turkey in1877. It was at this critical juncture that some Indian Muslim scholars gallantlyvolunteered to counter this threat, and to preserve the Islamic faith and heritageworldwide, despite the severe problems faced by the Muslims in India itself.This study highlights the role of an eminent scholar in this movement, namelyAllama Shibli Nu’mani (1857-1914), who in 1914 conceived the idea offounding the world-famous Islamic research institute Darul Musannefin ShibliAcademy in his home town of Azamgarh, Uttar Pradesh, India. Shibli was veryactive and instrumental in collecting donations from the wealthy landowners(zamindars) among the Muslim elite in his hometown of Azamgarh for theOttoman cause, raising 3,000 rupees, which was handed to Husain HasibAfendi, the Ottoman Consul in Bombay in 1877. Furthermore, his eloquentpoetry rallied Muslims across India to support the valour and heroism displayedin the jihad by Ghazi Usman Pasha against the Russians. Shibli travelled toIstanbul in 1892 and met with the Pasha, on whose efforts Tamgha-i Majidi(gold medal) was granted to Shibli on 13th Muharram, 1310/7th August, 1892.This article is based on Shibli’s major works in Urdu, particularly his arousingeulogies (qasaid), Turkish archival reports, newspapers and magazines, andsecondary sources in Urdu and English.